Perspektif Zakî Najîb Mahmûd tentang Ilmu dan Agama dalam Logika Positivisme - Ghozi Ghozi (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2011)
This article comprehensively examines Zakî Najîb Mahmûd’s thought on the logic of positivism on the relationship between religion and science. The study employs the literature interpretation method. The study encompasses the logic of positivism of Zakî Najîb Mahmûd, a confirmation map of knowledge on areas of science and religion, and the dichotomy of science and religion. The study finds that the logic of positivism formulated by Zakî Najîb Mahmûd has accommodated religious knowledge as a scientific matter, just like positive science in which its references can be mapped out through accountable epistemological aspects.